The Diagnostic and Prognostic Values of FOXP3 Gene in Iraqi Breast Cancer Women - Najm, Mohammed A. (Iraqi Journal of Cancer and Medical Genetics, 2016)
Background: The transcription factor forkhead-box protein P3 (FOXP3) have been identified to counteract the anti-tumor immune responses during tumor progression. In addition, by expressing FOXP3, tumor cells may evade effector T-cell responses, resulting in a survival benefit of the tumor. Objectives: Evaluation of the diagnostic and/or prognostic values of FOXP3 gene in breast cancer Iraqi female patients by initially comparing the expression concentrations of this gene between breast cancer patients and control group, then, comparing the expression levels of FOXP3 with certain clinical features among breast cancer patients (ages of patients, tumor grade, tumor stage and the presence or absence of metastasis). Material and Methods: The Foxp3 levels were determined in tissue samples (Formalin Fixed Paraffin Embedded Tissue “FFPE”) derived from 51 Invasive Ductal Carcinoma women and 33 benign breast tumor women (control group) were attended to the Medical City and Al-Yarmouk teaching laboratories / Baghdad – Iraq. The patients’ samples were subjected to total RNA extraction, and then to molecular study by using reverse transcription and quantitative real time PCR at Molecular Oncology Unit in Guy´s Hospital – Kings College / London – UK. Results: The FOXP3 gene expression was detected in 45 (88.23%) of breast cancer patients, also, the expression levels of this gene showed high significant increase in breast cancer patients compared to control group. Furthermore, there were a gradual increase in the FOXP3 expression concentrations with disease grades (highly significant) and stages (significant) progression in patients with primary breast cancer, moreover, the metastatic breast cancer patients showed high significant increase in FOXP3 levels compared to primary breast cancer patients. There were no significant differences in the levels of FOXP3 among the age groups of patients. Conclusions: The present study results reflect the potential utility of FOXP3 as noninvasive marker for detecting breast cancer even in the earliest cancer stages, also, they suggest that possibility of using this gene as an efficient molecular signature for detecting breast cancer disease progression, discrimination between different stages and grades of breast tumors, and it might be of value as a prognostic marker.